Reducing Acute Kidney Injury and Costs of Percutaneous Coronary Intervention by Patient-Centered, Evidence-Based Contrast Use: The Barnes-Jewish Hospital Experience. Issue 3 (March 2019) - Amin, Amit P.; Crimmins-Reda, Patricia; Miller, Samantha; Rahn, Brandon; Caruso, Mary; Funk, Meghan; Pierce, Andrew; Kurz, Howard I.; Lasala, John M.; Zajarias, Alan; Bach, Richard G.; Sintek, Marc A.; et al.
Abstract : Supplemental Digital Content is available in the text.